What is Qualitative Interviewing? - Edwards, Rosalind (The 'What is?' Research Methods Series, 2013)
This book is available as open access through the Bloomsbury Open Access programme and is available on bloomsburycollections.com. What is Qualitative Interviewing? is an accessible and comprehensive 'what is' and 'how to' methods book. It is distinctive in emphasising the importance of good practice in understanding and undertaking qualitative interviews within the framework of a clear philosophical position. Rosalind Edwards and Janet Holland provide clear and succinct explanations of a range of philosophies and theories of how to know about the social world, and a thorough discussion of how to go about researching it using interviews. A series of short chapters explain and illustrate a range of interview types and practices. Drawing on their own and colleagues' experiences Holland and Edwards provide real research examples as informative illustrations of qualitative interviewing in practice, and the use of a range of creative interview tools. They discuss the use of new technologies as well as tackling enduring issues around asking and listening and power dynamics in research. Written in a clear and accessible style the book concludes with a useful annotated bibliography of key texts and journals in the field. What is Qualitative Interviewing? provides a vital resource for both new and experienced social science researchers across a range of disciplines.